Microplastic Contamination Assessment in Urban Stormwater Runoff UsingHyperspectral Imaging and Machine Learning: A Case Study of the İzmirMetropolitan Drainage Network, Turkey (Aintelia Science Notes, 2025)
Microplastic (MP) pollution in urban stormwater systems represents a critical but undercharacterised environmental pathway, with stormwater runoff constituting a primary vector transporting terrestrially originating MPs to receiving water bodies. This paper presents a hyperspectral imaging and machine learning framework for rapid, non-destructive quantification and polymer-type classification of microplastics in stormwater samples collected from the İzmir Metropolitan Municipality drainage network, Turkey. A shortwave infrared (SWIR, 900 - 1700 nm) hyperspectral camera coupled to a conveyor-belt scanning platform acquires spectral data cubes from filtered stormwater membrane samples. A random forest (RF) classifier trained on spectral signatures of seven reference polymer types achieves a mean classification accuracy of 91.3% and a mean F1-score of 0.893 on held-out test samples. Gradient-boosted tree regressionmodels trained on environmental and catchment-scale predictor variables  including impervious surface fraction, traffic density, and antecedent dry period explain 76% of variance in MP particle concentration across 38 drainage sub-catchments (R² = 0.76, RMSE = 412 particles/L). SHAP analysis identifies impervious surface fraction and commercial land-use proportion as the dominant drivers of MP concentration. The framework enables basin-scale MP load mapping at operational throughput (80 samples/day) and provides decision-support outputs for targeted source-control intervention.